Implementation of Project-Based Learning in Physical Education During the Social Distancing Pandemic Covid -19 - Afif Khoirul Hidayat (STKIP Muhammadiyah Kuningan, 2021)
Policy for studying at home caused by the Covid-19 pandemic impacts the Physical Education learning in Schools. This research was held to identify the application of Project-Based Learning methods on Physical Education in enacting Social Distancing Pandemic Covid-19. The way applied in this research is a descriptive method with a quality approach by Creswell. This research is a Grade VIIa students of SMP N 2 Merauke that consists of 29 students. The instrument in this research is a motivation questionnaire, interview, and documentation. The results showed that the application of Project-Based Learning methods on Physical Education, which was conducted independently in each student's home, was done very well and provided a learning experience the same as face-to-face learning. This research concludes that Project Based Learning methods with a blended approach can be used as an example and guidelines of Physical Education teacher in teaching distance learning in the enactment of Social Distancing Pandemic Covid-19.